A New Concept of Specialized Standards to Improve the Quality of Higher Legal Education - Sholpan Tlepina; Marat Sarsembayev; Yerbol Abaideldinov; Venera Balmagambetova; Zhanerke Zukay (Emerging Science Journal, 2024)
This study analyzes specialized national and international legal acts and standards that enjoy national and international recognition and are relevant to ensuring the appropriate quality of higher legal education in Kazakhstan. Applying methods of logical and legal analysis, a global approach to comparing the practices of legal education within the country and abroad, the authors offer specific recommendations for improving specific standards of Kazakh legislation on education, namely, the adoption of the draft law “On Higher Education” in the republic; the introduction of the Socratic method in the lecture and educational process, creative vacations as a special type of professional development at law faculties of universities; the use of digital artificial intelligence tools at all stages of law students’ education; providing more practical training; and significant restructuring of the knowledge verification system in exams. It is concluded that improving the quality of legal education is necessary for training highly qualified lawyers for legal practice, and lawyers with an anti-corruption legal consciousness. The novelty of this study is determined by its unique thematic focus, since it concerns an unexplored domain of specialized legal norms in the legal education sector of Kazakhstan. In addition, this study is novel as it is the first study in the history of the Republic in terms of improving higher legal education with the help of legislative and international legal norms. The practical significance of this study lies in the regulations and practices proposed for implementation. Doi: 10.28991/ESJ-2024-08-04-09 Full Text: PDF